Frontiers of Quantum Chemistry - Kirtman, Bernard; Nakatsuji, Hiroshi; Ozaki, Yukihiro; Wojcik, Marek J. (Singapore : Springer Singapore : Imprint: Springer, 2018)
The purpose of this book is to convey to the worldwide scientific co mmunity the rapid and enthusiastic progress of state-of-the-art quantum chemistry. Quantum chemistry continues to grow with remarkable success particularly due to rapid progress in supercomputers. The usefulness o f quantum chemistry is almost limitless. Its application covers not onl y physical chemistry but also organic and inorganic chemistry, physics, and life sciences. This book deals with all of these topics. Frontiers of Quantum Chemistry is closely related to the symposium of the same n ame held at Kwansei Gakuin University at Nishinomiya, Japan, in Novembe r 2015. The book's contributors, however, include not only invited spea kers at the symposium but also many other distinguished scientists from wide areas of quantum chemistry around the world..
Rigorous and Empirical Approaches to Correlated Single Particle Theo ries -- Circular Dichroism Spectroscopy with the SAC-CI Methodology: A ChiraSac Study -- Frontiers of Coupled Cluster Chiroptical Response The ory -- Response Theory and Molecular Properties -- Response Properties of Periodic Materials Subjected to External Electric and Magnetic Fiel ds -- Quantum Chemical Methods for Predicting and Interpreting Second-O rder Nonlinear Optical Properties: from Small to Extended p-conjugated Molecules -- Embedding Methods in Quantum Chemistry -- Calculation of V ibrational Spectra of Large Molecules from their Fragments -- Describin g Molecules in Motion by Quantum Many-Body Methods -- Relativistic Time -Dependent Density-Functional Theory for Molecular Properties -- Warmin g Up Density Functional Theory -- Toward a Quantum Chemical Description of Molecular Properties and Chemical Reactions at Extreme Condition of Pressure -- Transition States of Spin-Crossing Reactions from Organome tallics to Biomolecular Excited States -- Electron Communications and Chemical Bonds -- Molecular Dynamics Simulations of Vibrational Spectra of Hydrogen-Bonded Systems -- Nuclear Quantum Effect and H/D Isotope E ffect on Hydrogen-Bonded Systems with Path Integral Simulation -- Vibra tional Linear and Nonlinear Optical Properties: Theory, Methods and App lication -- Ab Initio Molecular Dynamics Study on Photoisomerization Re actions: Applications to Azobenzene and Stilbene -- Density Functional Theoretical Studies on Chemical Enhancement of Surface-Enhanced Raman S pectroscopy in Electrochemical Interfaces -- Quantum Chemistry Studies of Overtones and Combinations.
Description based on publisher-supplied MARC data.
Keywords: Bioinformatics; Chemistry, Physical and theoretical; Computational biology; Condensed matter; Physical chemistry; Physical Chemistry; Computer Appl. in Life Sciences; Condensed Matter Physics; Theoretical and Computational Chemistry